Competing through sourcing: manufacturing firms in Bangladesh - Azim, Md. Shamimul (2018)
Manufacturing firms are confronted with the challenge to respond to uniqueness of customer demands, uncertain market environment and performance improvement. This study therefore, aimed to provide an integrated strategic model to manufacturing firms to overcome these challenges. The framework was comprised of sourcing strategy, competitive strategy, strategic flexibility, strategic capability and sourcing relationship quality to enhance the firm 's performance. To achieve this, a quantitative research approach was used to collect primary data and Structural Equation Modeling (SEM) was used to analyze the hypothesized effects. Data were collected from manufacturing firm situated in Bangladesh. This study found positive direct effect of exogenous variable; cost-leadership strategy, related product diversification, manufacturing capability and purchasing capability on firm performance and sourcing strategy. Differentiation strategy and unrelated product diversification have not direct effect on manufacturing firm's performance. In addition, sourcing strategy effect on firm performance was positive. Significant positive mediating effect of sourcing strategy was reported in between exogenous variables and firm performance. Moderating effect of sourcing relationship quality was found significant. Sourcing relationship quality therefore, strengthen the relationship of sourcing strategy and firm performance. Empirical evidence of proposed integrated framework was established, and this will help manufacturing firms to improve performance. Manufacturing firms can consider the strategic fit of the study variables and outcome which might help for appropriate decision making and remain competitive. This study also shed light on strategic management literature by approaching moderated mediation model.